A Cross-Sectional Study to Determine Urinary Tract Infections and Antibiotic Susceptibility Patterns among Pregnant Women attending Antenatal Clinic at Kawempe National Referral Hospital, Uganda. - Mugisha, Anthony; Mujuzi, Samuel; Akampurira, Andrew (Student’s Journal of Health Research Africa, 2022)
Background: Urinary Tract Infection (UTI) is a disease of the urinary system. This type of infection involves urethritis, pyro nephritis, or cystitis. Symptoms can be pelvic pain, increased urge to urinate, pain on passing out urine, and blood in the urine (blander infections). A kidney UTI may cause back pain, nausea vomiting, and fever. Methods: This study was a cross-sectional-quantitative study carried out among 300 pregnant mothers attending ANC at Kawempe regional referral hospital in August 2021. Questionnaires were administered to get the biodata of Participants. Urine samples were collected using sterile containers. Urine culture was performed, urine chemistry using ten parameter strip then urine microscopy was done. Chemistry was done using ten parameter strips, urine microscopy and then later culture and sensitivity was done on urine samples with proteinuria. Results: Urine samples with proteinuria were 5.7 % (n=17), more than half of the Urine Samples 52%( n=156) had positive White blood cell cells and 48 %( n=144) had no abnormality detected. Culture on urine samples showed the following isolation, Escherichia.coli 24.3 %( n=9), Klebsiella pneumonia 21.6 %( n=8), Pseudomonas euroginosa 18.9 %( n=7) Staphylococcus aureus 16.22 %(n=6) Enterococcus spp 2.7%(n=1) and Candida albicans16.2 %( n=6). Conclusion: UTI is an infection of some part of your body’s urinary system which may include: kidneys, ureters, bladder, and urethra. Organisms causing UTIs in pregnancy are the same uropathogens that commonly cause UTI in non-pregnant patients with Escherichia coli being the most commonly isolated organism. Other bacteria include klebishella pneumoniae, staphulococuus, streptococcus, enterococcus, and pseudomonas. Recommendations: Kawempe National Referral Hospital. Should improve the Laboratory to perform microbiology tests.